Communication perspectives on tourist decision making in community-based tourism: Hua Takhe case - kaewoui, Natvara; Kaewnuch, Kanokkarn (Universitas Padjadjaran, 2025)
Background: Community-based tourism (CBT) involves local communities in the tourism value chain to provide sustainable benefits. Tourist decision-making in CBT situations, specifically how communication elements like destination image, service quality, and local engagement affect behavior, is currently understudied. Recent work typically separates these elements without acknowledging their interconnections in tourist decision-making. Purpose: This study aims to develop a conceptual model that explains tourist decision-making in community-based tourism (CBT) by integrating key communication determinants. It focuses on how communication factors such as destination image, service quality, community storytelling, and local engagement interact to influence tourist behavior. Methods: A qualitative-descriptive approach was employed through an integrative literature review of empirical and conceptual studies from tourism and communication disciplines. Relevant sources were systematically selected based on thematic relevance to CBT, communication, and tourist behavior, allowing the synthesis of theoretical and contextual insights. Results: The findings show that symbolic, emotional, and communicative dimensions of tourism services significantly shape tourists’ decision-making in CBT contexts. Authentic encounters and emotional connections between tourists and host communities enhance destination image and perceived service quality. Furthermore, cultural immersion, local narratives, and place-based identities strengthen perceived value, loyalty, and revisit intention. Conclusion: This study demonstrates that CBT tourist decisions extend beyond rational or economic considerations. Communication factors particularly interpersonal connection, narrative meaning-making, and perceived authenticity play a central role in shaping tourist choices and behavioral intentions within community-based destinations. Implications: Theoretically, this study enriches CBT literature by embedding communication variables into behavioral models. Practically, it offers strategic recommendations for enhancing community storytelling, destination branding, and service interaction especially in destinations like Hua Takhe.